Bird Species in the Agroforestry Areas of Karang Intan District, Banjar Regency, Indonesia - Ismail Marsuki; Mochamad Arief Soendjoto; Eko Rini Indrayatie (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2022)
Data on birds in agroforestry areas of South Kalimantan are not yet available. The purpose of the study was to analyze bird species that use agroforestry areas as habitats. The sample locations are the agroforestry areas of Kiram Village, Biih Village, and Pulau Nyiur Village, Karang Intan District, Banjar Regency. Diurnal bird species were observed and individuals were counted at 07.00-10.00 and 15.00-18.00 with five replications and the point count method in October 2021. Only a point count was placed in each village. Observational aids are binoculars and a prozumer camera. Twenty-five bird species were found in all agroforestry areas of Karang Intan District. Species and individual birds spread differently at each sample location. The index of bird species diversity from the highest to the lowest is the agroforestry area of Pulau Nyiur (2.63), Biih (2.47), and Kiram (2.43). Although the community similarity index differs between calculations based on the number of species and based on the number of individuals, the order of similarity from highest to lowest is the same, namely Kiram-Biih, Kiram-Pulau Nyiur, and Biih-Pulau Nyiur. Because it is also a suitable habitat for protected or threatened birds, agroforestry areas can be maintained and even improved as natural conservation areas